Simulation Tests of Extinguishing Process Using Mist Nozzles With Application of Hybrid Fire Model - Gałaj, Jerzy; Konecki, Marek; Šukys, Ritoldas (Journal of Civil Engineering and Management, 2016)
The article presents a computer model of the fire extinguishing process using mist nozzles. A previously developed hybrid fire model was used for this purpose. Assumptions and relationships were given to represent a mathematical model of extinguishing process, which comprises a unique approach to the determination of sprinkling area in an elementary cell of field fire model. A description of simulation tests of the model was given for several different input data, differing by mean diameters of droplets. This enabled a study of their effects on such output parameters as received heat flux, temperature and rate of its growth. For one selected computational cell located on the axis of the nozzle at floor level having the coordinates [10, 10, 1], the obtained results were presented in the form of heat flux and temperature. To simplify the analysis, characteristic parameters of particular curves were listed in the table. Conclusions formulated on the basis of results obtained during tests were specified at the end of work. They confirmed the expected regularity assuming that the extinguishing process was more effective in the case of droplets of a smaller diameter and greater sprinkling intensity. This allows assessing the degree, to which these stream parameters affect the extinguishing effectiveness.